Effects of epidermal growth factor on atrophic enteritis in piglets induced by experimental porcine epidemic diarrhoea virus - Jung, Kwonil (Vet J, 2008)
Epidermal growth factor (EGF) promotes gastrointestinal mucosal recovery by stimulating the mitogenic activity of intestinal crypt epithelial cells. The aim of this study was to determine the effects of EGF on atrophic enteritis induced in piglets by experimental infection with porcine epidemic diarrhoea virus (PEDV) strain Dr13. Two groups of 12 conventional, colostrum-deprived, 1-day-old, large White-Duroc cross breed piglets were inoculated orally with PEDV (3 × 10(5) 50% tissue culture infective doses), with or without EGF (10 μg/kg/day, intraperitoneally once daily for 4 days after infection) and compared to 12 uninfected, untreated control piglets. PEDV + EGF piglets had less severe clinical signs than PEDV only piglets at 48 and 60 h post-infection (hpi). Histologically, the ratio of villous height:crypt depth of PEDV + EGF piglets was significantly higher than PEDV only piglets at 36 and 48 hpi. Immunohistochemistry for Ki67 demonstrated increased proliferation in intestinal crypt epithelial cells of PEDV + EGF piglets compared to PEDV only piglets at 36, 48 and 60 hpi. EGF stimulates proliferation of intestinal crypt epithelial cells and promotes recovery from atrophic enteritis in PEDV-infected piglets.